Vitamin D3 alleviates nonalcoholic fatty liver disease in rats by inhibiting hepatic oxidative stress and inflammation via the SREBP-1-c/ PPARα-NF-κB/IR-S2 signaling pathway - Reda, Doha; Elshopakey, Gehad E.; Albukhari, Talat A.; Almehmadi, Samah J.; Refaat, Bassem; Risha, Engy F.; Mahgoub, Hebatallah A.; El-Boshy, Mohamed E.; Abdelhamid, Fatma M. (Frontiers in Pharmacology, 2023)
Introduction: Nonalcoholic fatty liver disease (NAFLD) is a chronic disease characterized by fat deposits in liver cells, which can lead to hepatitis and fibrosis. This study attempted to explore the protective effect of vitamin D3 (VitD) against NAFLD. Methods: Adult male albino rats were randomized into four separate groups: the negative control group was fed a standard rat chow; the positive group received a high-fat diet (20%) and 25% fructose water (NAFLD); the VitD control group was intramuscularly treated with VitD (1,000 IU/kg BW) 3 days per week for 10 weeks; and the NAFLD group was treated with VitD therapy. Biochemical and hepatic histological analyses were performed. Hepatic oxidative stress and inflammatory conditions were also studied. Hepatic expression of sterol regulatory element-binding protein 1-c (SREBP-1-c), peroxisome proliferator-activated receptor alpha (PPAR-α), and insulin receptor substrate-2 was analyzed by quantitative real-time polymerase chain reaction. Results and discussion: The NAFLD rats exhibited elevated terminal body weight, hepatic injury markers, dyslipidemia, glucose intolerance, and insulin resistance. Moreover, the NAFLD rats had increased SREBP-1-c expression and reduced PPAR-α and IRS-2 expressions. Histological analysis showed hepatic steatosis and inflammation in the NAFLD group. In contrast, VitD administration improved the serum biochemical parameters and hepatic redox status in NAFLD rats. Also, VitD treatment ameliorated hepatic inflammation and steatosis in the NAFLD group by decreasing the expression of SREBP-1-c and increasing the expression of PPAR-α. Overall, these results suggest that VitD could have a protective effect against NAFLD and its associated complication.